Anomalous Origin of the Right Coronary Artery from the Pulmonary Artery Diagnosed as an Incidental Finding. (6th January 2012) - Contreras, Alejandro E.; Leonardi, Carlos; Lazzarin, Omar; Bagur, Rodrigo; Peirone, Alejandro
ABSTRACT A 2‐year‐old boy was referred for evaluation of a systolic heart murmur. Two‐dimensional Doppler echocardiogram showed an abnormal flow through the interventricular septum, directed upward and toward the posterior wall of the main pulmonary artery. Left coronary angiogram showed a normal distribution of the anterior descending and circumflex arteries. The right coronary artery (RCA) was fully filled through collaterals from the left coronary system, and arising from the main pulmonary artery. Successful surgical reimplantation of the RCA was undertaken. Although uncommon, it is important to recognize the anomalous origin of the RCA arising from the pulmonary artery since it can be associated with serious adverse cardiac events.